2015
DOI: 10.1002/gete.201400022
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the penetration process of ship anchors in sand

Abstract: In order to study the burial depth of submarine power cables in the German North Sea, the penetration process of ships' anchors in seabed soil was simulated by using the coupled Eulerian–Lagrangian method in Abaqus/Explicit. In the 3D finite element model the sandy seabed was simulated with different densities under both drained and undrained conditions. The resulting penetration mechanism of a ship anchor in sand was verified by field test data. It showed that under specific conditions the penetration depth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
(21 reference statements)
0
10
0
1
Order By: Relevance
“…This depth, namely the maximum fluke depth, is important for the risk of damage to a submarine cable. Grabe et al [9] observed in numerical simulations and field tests (see also [4]) three varying penetration depths, which have to be differentiated. Fig.…”
Section: Anchor Penetration In Sandmentioning
confidence: 99%
See 3 more Smart Citations
“…This depth, namely the maximum fluke depth, is important for the risk of damage to a submarine cable. Grabe et al [9] observed in numerical simulations and field tests (see also [4]) three varying penetration depths, which have to be differentiated. Fig.…”
Section: Anchor Penetration In Sandmentioning
confidence: 99%
“…Ivanovic et al simulated the penetration of fishing gear into the subsoil using a three‐dimensional FE model with adaptive remeshing technique. Grabe et al and Grabe and Wu modelled the penetration process of anchors in sand and clay using a CEL approach that is described below.…”
Section: Previous Research Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the large soil-plate displacements cannot be captured with the standard Lagrangian FEM because of issues with element distortions, Arbitrary Lagrangian-Eulerian methods (ALE) and particle-based methods have been developed in the last few decades (Atluri & Zhu, 2000;Donea & Huerta, 2004). Among them, the remeshing and interpolation technique with small strain (RITSS) method (Hu & Randolph, 1998), the coupled Eulerian-Lagrangian (CEL) method (Grabe, Qiu, & Wu, 2015;Qiu, Henke, & Grabe, 2011), and the Material Point Method (MPM) (Sulsky, Chen, & Schreyer, 1994) have been successfully applied in soil penetration problems similar to the anchor pull out discussed in this paper Mahmoodzadeh & Randolph, 2014;Phuong, van Tol, Elkadi, & Rohe, 2016;Tian, Cassidy, Randolph, Wang, & Gaudin, 2014).…”
Section: Introductionmentioning
confidence: 99%